Characterization of glycan isomers using magnetic carbon nanoparticles as a MALDI co-matrix. Issue 35 (27th June 2019) - Banazadeh, Alireza; Nieman, Reed; Goli, Mona; Peng, Wenjing; Hussein, Ahmed; Bursal, Ercan; Lischka, Hans; Mechref, Yehia
Abstract : Magnetic carbon nanoparticles as a MALDI co-matrix enable isomeric characterization of glycans in biological samples. Abstract : Matrix-assisted laser desorption ionization-in source decay (MALDI-ISD) analysis is a useful technique in the structural analysis of glycans. Our recent publication demonstrated that magnetic carbon nanoparticles (MCNPs), used as a MALDI co-matrix, significantly enhanced ISD efficiency for glycomic analysis by MALDI-TOF. In this study, MCNPs were used for the structural study of isomeric glycans. Results from the standard glycans confirmed easy distinction of positional and linkage isomers without the need for further derivatization of glycan molecules. Extensive glycosidic and cross-ring fragmented ions provided different fragment patterns for various glycan isomers. Core- and branch-fucosylated isomers were distinguished by several unique ions, and pseudo-MS 3 data were used to recognize the fucosylated branch. Although no diagnostic fragment ion was observed for 2, 3- and 2, 6-linked sialic acid isomers, their MALDI-ISD patterns were found to be significantly different ( P < 0.05). Furthermore, the method introduced in this study could not only be used for the identification of glycan isomers but has also proved effective for the isomeric structural confirmation of gangliosides. GD1a and GD1b gangliosides were easily distinguished by the diagnostic ion originated from GD1a, produced by Z4α Z2β cleavages. Moreover, liquid chromatography coupled with MALDI-TOF was applied to analyze N -glycan isomers derived from a pooled human blood serum sample, providing an alternative method of isomeric glycomic analysis of biological specimens.